The Real Incidence of Extracapsular (Satellite) Cysts of Liver Echinococcus. Issue 4 (1999) - Voros, Dionysios; Kalovidouris, Angelos; Gouliamos, Athanasios; Vlachos, Lambros; Danias, Nickolaos; Papadimitriou, John
Abstract : Background: The presence of extracapsular (Satellite) cysts in liver echinococcus granulosus is known for many years. In one of our previous studies of radiological (CT) material they were found to be present in 16% of cases. Methods: In the present study the operative findings, in cases of total capsectomy (cystopericystectomy) or partial lobectomy are presented. Results: The real incidence of these cysts in operative specimens was as high as 29, 5%. They were present in 15 out of 51 totally excised cysts. Conclusions: We conclude that satellite cysts are present more often than they are radiologically detected. As they can be incriminated as a cause of recurrence of the disease they must be excised en block with the main parasitic cysts, by means of more radical procedures such as cystopericystectomy or partial hepatectomy, whenever it is feasible.